The Importance of Ethics in Writing Scientific Papers - Ainis Syifa Nasution; Vebriantin; Zacky Aulia Nasution; Luqman Hakim (ISNU Sumatera Utara, 2025)
Writing scientific papers is a form of academic activity that demands intellectual and moral responsibility from every writer. Ethics in scientific writing is an essential element in maintaining the integrity, honesty, and credibility of scientific results. In the context of higher education and research, the application of academic ethics plays a crucial role in creating a healthy and responsible academic culture. This article discusses in depth the concept of academic ethics in scientific writing, including the basic principles underlying it, such as originality, accuracy, and respect for intellectual property rights. Ethical elements that must be upheld by authors, as well as various forms of ethical violations such as plagiarism, fabrication, and data falsification, are also comprehensively discussed. Furthermore, this article proposes preventive measures and practical strategies that can be implemented to maintain and uphold ethics throughout the scientific writing process. By consistently understanding and applying academic ethics, it is hoped that the quality and credibility of scientific works can be maintained and make a positive contribution to the development of science.